2019
DOI: 10.1021/acsami.9b16509
|View full text |Cite
|
Sign up to set email alerts
|

Robust Superhydrophobic Conical Pillars from Syringe Needle Shape to Straight Conical Pillar Shape for Droplet Pancake Bouncing

Abstract: Superhydrophobic conical pillars have great industrial application potential in, for example, anti-icing of aircraft wings and protecting high voltage transmission lines from freezing rain because of their droplet pancake bouncing phenomenon which is recognized to furthest reduce the liquidsolid contact time. However, there are still no methods that can large-scale fabricate robust

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Comparing with other state-of-the-art coating methods, our method uses only OTS and water to create hierarchical micro/ nanostructure template with low surface tension in a single step, and demonstrates superior wettability and anti-abrasion property (Supplementary Table 3) 6,[8][9][10]43,[46][47][48][49][50][51][52][53] . In comparison, most other strategies relied on the modification of "pre-made" rough structures with low surface tension coatings.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with other state-of-the-art coating methods, our method uses only OTS and water to create hierarchical micro/ nanostructure template with low surface tension in a single step, and demonstrates superior wettability and anti-abrasion property (Supplementary Table 3) 6,[8][9][10]43,[46][47][48][49][50][51][52][53] . In comparison, most other strategies relied on the modification of "pre-made" rough structures with low surface tension coatings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13,29,30,32,40,41 ] The gray dashed line in Figure 5 represents the inertia–capillary limit (i.e., 2.2τ) for a spherical droplet. Studies have reported that t c values lower than the inertia–capillary limit were obtained on SHB surfaces at room temperature because of pancake bouncing [ 20,38,39 ] and axial symmetry breaking. [ 18,19 ] Other studies have also revealed that t c values lower than the limit were obtained on HP surfaces at high temperatures due to jet bouncing on a silicon nanowire surface, [ 13 ] explosive pancake bouncing on a nanoscale honeycomb copper surface, [ 30 ] and an asymmetric bubble momentum force on a SiN x surface with v‐shaped microgrooves.…”
Section: Resultsmentioning
confidence: 99%
“…The spine and barbs have micro/nano roughness. [44][45][46][47][48][49][50][51][52] Wettability can be evaluated by measuring the contact angle (CA) and sliding angle (SA) of a small liquid droplet on the target substrate. CA refers to the angle (θ) between the tangent of the air/liquid surface and the liquid/solid interface at the three-phase contact line when a droplet drops on a surface.…”
Section: Nature Creatures With Gradient Surfacesmentioning
confidence: 99%